1997
DOI: 10.1002/(sici)1099-0992(199701)27:1<1::aid-ejsp802>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

When the survey question directs retrieval: Implications for assessing the cognitive and affective predictors of global evaluation

Abstract: Research suggests that individuals do not respond to survey questions on the basis of a single, fixed set of psychological considerations. To the contrary, they respond on the basis of whatever material happens to come to mind at the moment of answering. Furthermore, the particular material that comes to mind often depends upon the nature of the question and the manner in which it is posed. This has important implications when attempting to assess the independence of beliefs and emotions as predictors of globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In our study, we asked respondents to focus on what made them worried about immigration. We modeled this manipulation on those used by social psychologists (Fischhoff et al, 2003;Isbell & Ottati, 2002;Lerner & Keltner, 2001;Ottati, 1997;Roseman, Spindel, & Jose, 1990;Smith & Ellsworth, 1985) as well as political scientists (Valentino et al, 2009;Valentino et al, 2008) who found that by asking respondents to go through an exercise of listing their worries that individuals experienced and reported increased anxiety. One advantage of this method is that emotion generation using language increases self-reported negative affect as well as amygdala activation more consistently than do methods that include visual stimulation (McRae, Misra, Prassad, Pereira, & Gross, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…In our study, we asked respondents to focus on what made them worried about immigration. We modeled this manipulation on those used by social psychologists (Fischhoff et al, 2003;Isbell & Ottati, 2002;Lerner & Keltner, 2001;Ottati, 1997;Roseman, Spindel, & Jose, 1990;Smith & Ellsworth, 1985) as well as political scientists (Valentino et al, 2009;Valentino et al, 2008) who found that by asking respondents to go through an exercise of listing their worries that individuals experienced and reported increased anxiety. One advantage of this method is that emotion generation using language increases self-reported negative affect as well as amygdala activation more consistently than do methods that include visual stimulation (McRae, Misra, Prassad, Pereira, & Gross, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…(Crites et al 1994). There is a useful literature on using self-report to measure emotional responses (Bagozzi 1993;Watson & Clark 1994;Mehrabian 1995Mehrabian , 1996Ottati 1997;Watson et al 1988; also see . The measurement of emotional responses to a target stimulus must take into account whether the focus is on the global character of the target or on some specific properties thereof (Ottati 1997).…”
Section: Methodological Quandariesmentioning
confidence: 99%
“…Excellent overviews include those by Zajonc (1998) and Cacioppo & Gardner (1999). More specific review topics have included feelings as subjective experience (Schwarz & Clore 1996); the interrelationship of emotion and memory (Blaney 1986); the relationship between emotion and motivation (Bradley 2000); the roles of emotion in evaluation (Tesser & Martin 1996), political judgment (Ottati 2000), and electoral politics (Glaser & Salovey 1998); and the neuroscience of emotion (Damasio 1994, LeDoux 1996, Rolls 1999). In addition, there are two collections of important papers on emotion, one published some 20 years ago (Rorty 1980) and one more recent (Ekman & Davidson 1994).…”
Section: Recent Reviewsmentioning
confidence: 99%
“…Similarly, judgments about social categories depend on the specific category exemplars that happen to be activated at that moment (Smith & Zarate, 1992). Moreover, studies of context effects (Ottati, 1997;Schwarz, 1994;Tourangeau & Rasinski, 1988) and the results of introspection (Tesser, 1978) have supported the idea that "people often have a large and conflicting 'data base' relevant to their attitudes on any given topic, and the attitude they have at any given time depends on the subset of these data to which they attend" (Wilson & Hodges, 1992, p. 38). Attitude reports can change from one time to the next without any additional information about the attitude object, simply because the context of the moment makes a biased subset of knowledge about that topic cognitively accessible (see Schwarz, 1998, for a comprehensive review).…”
Section: Attitude Changementioning
confidence: 99%